Targeted Tuition Delivered by Personal Videoconferencing for Students with Mathematical Learning Difficulties. Issue 2 (1st February 2018) - Kestel, Eugénie; Forgasz, Helen
Abstract: The effectiveness of an individual, conceptual instruction‐based tuition program delivered by personal videoconferencing (PVC), compared to face‐to‐face (FtF) delivery for 30 upper primary and middle school students with mathematical learning difficulties (MLD), is described in this article. The experimental intervention targeted number sense, conceptual understandings of mathematical operations, and fluency with basic number facts. Results showed that significant improvements were achieved in accuracy on basic number fact tasks and standardized test results for both experimental groups. Implications for students with MLD living regionally and remotely are discussed.